KOMUNIKASI POLITIK KELOMPOK RADIKAL PADA PORTAL MEDIA VOAISLAM.COM DAN ARRAHMAH.COM PERSPEKTIF HAROLD. D LASSWELL - Achmad Tohari; Bany Prayogi (Universitas Tribhuwana Tunggadewi, 2022)
Abstract. Modernization makes all access to the delivery of communication and information fast and easy. However, access is often used for various things that lead to negative actions, such as radicalism groups who try to spread their ideology through media labeled as da'wah such as the sites voaislam.com and arrahmah.com in Harold's perspective. D Lasswell. The type of research used is descriptive qualitative with literature study method. The focus of this theoretical analysis uses the analysis of political communication media by Harold D. Lasswell. The results showed that voaislam.com and arrahmah.com as da'wah sites highly uphold the principles of Islamic law so that this fanaticism often causes confrontation. Communicators, messages, media and effects in the analysis of political communication play an important role because each of these units can foster belief in the